2018
DOI: 10.1113/jp275661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine on the fetal transcriptomic response to umbilical cord occlusion: comparison with hypoxic hypoxia in the cerebral cortex

Abstract: Umbilical cord occlusion (UCO) is known to cause neurological disorders in the neonate. Previously, we have reported that hypoxic hypoxia (HH) stimulates the appearance of bacteria in the fetal brain and upregulates the expression of inflammatory markers in fetal cerebral cortex (CTX) and also that ketamine attenuates these responses. In the present study, we aimed to test the hypothesis that UCO, similar to HH, produces an inflammatory response in the fetal CTX and also that treatment with ketamine reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In the late-gestation fetus, umbilical cord occlusion poses an immediate threat to fetal survival, whereas transient hypoxic hypoxia is better R5 tolerated. Despite this logic, we found that the transcriptomics response to hypoxic hypoxia is more vigorous than the response to asphyxic hypoxia of the same magnitude (148). This difference is illustrated in Fig.…”
Section: Responses One Day After Hypoxiamentioning
confidence: 75%
See 1 more Smart Citation
“…In the late-gestation fetus, umbilical cord occlusion poses an immediate threat to fetal survival, whereas transient hypoxic hypoxia is better R5 tolerated. Despite this logic, we found that the transcriptomics response to hypoxic hypoxia is more vigorous than the response to asphyxic hypoxia of the same magnitude (148). This difference is illustrated in Fig.…”
Section: Responses One Day After Hypoxiamentioning
confidence: 75%
“…We reasoned that it is important to understand whether a transient hypoxic hypoxia, lowering maternal Pa O 2 from 100 tõ 50 mmHg [equivalent to travel to 12,000-feet elevation (101)], disturbs gene expression in the fetal brain in the longer term, in this case 1 day later. We compared the responses at 1 day with responses at 1 h after hypoxic hypoxia, and we compared the responses to hypoxic hypoxia with the responses to asphyxic hypoxia (partial umbilical cord occlusion performed in such a way that the change in fetal Pa O 2 was similar to that caused by hypoxic hypoxia) (147,148). The assumption, from the perspective of the fetal physiologist, is that the fetus responds to changes in blood gases (decreased Pa O 2 or, in the case of asphyxic hypoxia, decreased Pa O 2 and increased Pa CO 2 ) and that, at the end of the hypoxic event, the fetus is returned to the prehypoxia functional state after the physiological response that redistributes combined ventricular output to the fetal brain and heart.…”
Section: Responses One Day After Hypoxiamentioning
confidence: 99%
“…We have reported the surprising discovery that bacteria can enter the fetus after transient maternal hypoxia 9 . In several studies, we found that isobaric maternal ventilatory hypoxia stimulated an inflammation-like response in the fetal brain 10,11 and kidneys 12 that correspond to the transcriptomics and cellular response that would be expected after bacterial infection. Indeed, culture and nonculture-based techniques confirmed the appearance of bacteria in the fetal brain, and confirmed that the bacteria matched those found in the placenta 9 .…”
mentioning
confidence: 78%
“…Tissues were either flash frozen with liquid nitrogen for DNA and protein analysis, chilled on wet ice and immediately sent for culturing analysis, or fixed in 4% paraformaldehyde overnight (followed by dehydration and paraffin embedding) for histological analysis. These methods of specimen collection and preservation have been previously described 10 , 13 , 31 . The time course of inoculation, blood sampling, and euthanasia/tissue collection in study 2 was similar to that of study 1 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Immune function and types of physiological insults are also explored by Zarate and colleagues, who demonstrate that the nature of a hypoxic stimulus can modify posthypoxic responses by the fetus (Zarate et al . ). Whereas, maternal hypoxic‐hypoxia led to an increase in inflammation mediators and immune cells in the fetal brain transient, partial umbilical cord occlusion producing a similar level of hypoxia did not, but instead modulated genes related to metabolism.…”
mentioning
confidence: 97%